ANALYSING THE VALUES OF EQUALITY AND FREEDOM IN THE NATIONAL CURRICULUM 2013 FOR SENIOR SECONDARY SCHOOLS IN INDONESIA - Lestari, Sri (Universitas Esa Unggul, 2020)
AbstractThe context of developing a curriculum in Indonesia is indeed unique yet challenging, considering the widespread of the archipelago and its diverse society. It leads to differences in the ease for children to access education and for the government to develop the curriculum. which results in inequality. The limited capacity to develop the centralized curriculum has made inequality in educational access and it remains unsolved. In a democratic society where equality and freedom become its characteristics, the curriculum should be the central role to empower learners to engage in the modern democratic society and to adapt to the rapid global changes. It is indicated by their ability to participate in transformation and problem solving through communication, creativity, and collaboration. This paper explores the values of equality and freedom in the National Curriculum 2013 for senior secondary schools in Indonesia as the guideline for schools to set their objectives and for teachers to deliver the knowledge. It is to find out whether the curriculum development is based on those values and how equality and freedom are inculcated in the curriculum implementation. This centralized curriculum has focused on knowledge rather than emphasized on democratic values to live in freedom and equal society. Therefore, the values of democracy in the development of the National Curriculum for senior secondary schools in Indonesia are just rhetoric.Ã‚Â Ã‚Â Keywords: curriculum development, democracy in education, national curriculumÃ‚Â AbstrakKonteks pengembangan kurikulum di Indonesia cukup unik dan menantang dengan luasnya kepulauan dan masyarakat yang majemuk. Hal ini mengarah pada perbedaan bagi anak-anak untuk mengakses pendidikan dan bagi pemerintah untuk mengembangkan kurikulum, sehingga mengakibatkan kesenjangan. Terbatasnya kapasitas untuk mengembangkan kurikulum terpusat menimbulkan kesenjangan dalam akses pendidikan yang terus menjadi masalah. Dalam masyarakat demokratis, yang bercirikan kesetaraan dan kebebasan, kurikulum seharusnya memegang peran utama untuk memberdayakan pembelajar ikut serta dalam masyarakat demokratis and beradaptasi dengan perubahan global. Hal ini ditandai dengan kemampuan berpartisipasi dalam perubahan sosial dan pemecahan masalah dalam masyarakat melalui komunikasi, kreativitas dan kolaborasi. Artikel ini menggali nilai-nilai kesetaraan dan kebebasan yang terkandung dalam Kurikulum Nasional 2013 untuk sekolah menengah atas di Indonesia yang merupakan panduan bagi sekolah untuk menentukan tujuan dan bagi guru untuk menyampaikan ilmu. Selain itu, artikel ini akan mengulas apakah kurikulum tersebut berdasarkan nilai-nilai tersebut dan bagaimana nilai-nilai tersebut ditanamkan dalam implementasi kurikulum. Kurikulum yang terpusat lebih fokus pada ilmu pengetahuan daripada nilai-nilai demokrasi untuk hidup dalam masyarakat. Maka, nilai-nilai demokrasi dalam pengembangan kurikulum nasional untuk sekolah menengah atas di Indonesia masih sebatas retorika.Ã‚Â Kata kunci: pengembangan kurikulum, demokrasi dan pendidikan, kurikulum nasional